Effectiveness and safety of hydrogen inhalation as an adjunct treatment in Chinese type 2 diabetes patients: A retrospective, observational, double-arm, real-life clinical study - Zhao, Ziyi; Ji, Hongxiang; Zhao, Yunsheng; Liu, Zeyu; Sun, Ruitao; Li, Yuquan; Ni, Tongshang (Frontiers in Endocrinology, 2023)
Aim: To analyze the effectiveness and safety of hydrogen inhalation (HI) therapy as an adjunct treatment in Chinese type 2 diabetes mellitus (T2DM) patients in a real-life clinical setting. Methods: This observational, non-interventional, retrospective, double-arm, 6-month clinical study included T2DM patients receiving conventional anti-diabetes medication with or without HI initiation from 2018 to 2021. Patients were assigned to the HI group or non-HI group (control group) after 1:1 propensity score matching (PSM). The mean change in glycated hemoglobin (HbA1c) after 6 months in different groups was evaluated primarily. The secondary outcome was composed of the mean change of fasting plasma glucose (FPG), weight, lipid profile, and homeostasis model assessment. Logistics regression was performed to evaluate the likelihood of reaching different HbA1c levels after 6-month treatment between the groups. Adverse event (AE) was also evaluated in patients of both groups. Results: In total, 1088 patients were selected into the analysis. Compared to the control group, subjects in HI group maintained greater improvement in the level of HbA1c (-0.94 % vs -0.46 %), FPG (-22.7 mg/dL vs -11.7 mg/dL), total cholesterol (-12.9 mg/dL vs -4.4 mg/dL), HOMA-IR (-0.76 vs -0.17) and HOMA-β (8.2 % vs 1.98 %) with all p < 0.001 post the treatment. Logistics regression revealed that the likelihood of reaching HbA1c < 7 %,  7 % to  8 % and > 1 % reduction at the follow-up period was higher in the HI group, while patients in the control group were more likely to attain HbA1c  9 %. Patients in HI group was observed a lower incidence of several AEs including hypoglycemia (2.0 % vs 6.8 %), vomiting (2.6 % vs 7.4 %), constipation (1.7 % vs 4.4 %) and giddiness (3.3% vs 6.3 %) with significance in comparison to the control group. Conclusion: HI as an adjunct therapy ameliorates glycemic control, lipid metabolism, insulin resistance and AE incidence of T2DM patients after 6-month treatment, presenting a noteworthy inspiration to existing clinical diabetic treatment.